DESIGN OF LUBRICANTS FOR CNG-CONVERTED GASOLINE ENGINES - Setyo Widodo; Muhammad Hanifuddin; Milda Fibre (Testing Center for Oil and Gas LEMIGAS, 2016)
The objective of this study is to develop a lubricant formula for the gasoline engine that has been converted to compressed natural gas (CNG-fueled). The lubricant specification is SAE 15W40 API SL. This study was conducted in six stages, namely; i). lubricant formulation, ii). laboratory scale production, iii). Laboratory analysis, iv). pilot scale production and laboratory analysis, v). test performance through bench test or a road test, vi). final data analysis and evaluation. A laboratory test of physical and chemical properties of lubricants refers to the Indonesian National Standard (SNI), followed by road tests up to the mileage of 10,000 kilometers. The result showed that the lubricant formula obtained can work well to 10,000 kilometers.